Monitoreo de Condición en Motores de Combustión Interna Monocilíndricos con Base en Adquisición y Procesamiento de Señales Experimentales - Torres M, Daniela; Quintero R, Héctor F.; López L, Juan F.; Orozco G, Álvaro A. (KnE Engineering, 2018)
In recent years, condition monitoring based on signal analysis has become a valuable tool for the diagnosis of internal combustion engines. In this paper the experimental design for the ICE monitoring condition, based on signal analysis, is presented. The experimental configuration was development for the analysis of signals from ICE in order to monitor their condition. The conduced case study consists on the monitoring condition of a single-cylinder engine, operating under regular conditions and different speeds. The instrumentation, the adquisition systems as well as the signals analysis are also presented. The adquired signals were: engine block vibration, in-cylinder pressure and crankshaft speed. The mentioned signals were analyzed and processed by FFT and Rigid Regression. It was possible to obtain the frequency spectrum of the vibration signal and reconstruct the in-cylinder pressure of the single-cylinder engine. The presented configuration can be taken as a basis for the evaluation of others engines and for improving the schemes of monitoring condition. Keywords: Internal combustion engines, condition monitoring, signal acquisition, signal processing.